2017
DOI: 10.1016/j.jprot.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of SOMAscan to LC-MS/MS and RNA-seq for quantitative profiling of human embryonic and mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSC) represent promising stem cell-derived therapeutics as indicated by their application in >500 clinical trials currently registered with the NIH. Tissue-derived MSC require invasive harvesting and imply donor-to-donor differences, to which embryonic stem cell (ESC)-derived MSC may provide an alternative and thus warrant thorough characterization. In continuation of our previous study where we compared in depth embryonic stem cells (ESC) and MSC from two sources (bone marrow and ESC-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The distribution for 6903 intersecting features is depicted in Fig. 5A with average correlation of 0.5 and a mode at 0.9 demonstrating better correlation than previously published for somatic cells (0.4) (49)or differentiating cells (0.2) (48), but in line with our previous study (50). PCA analysis was performed on differentially expressed features, which display good correlation (R Ͼ 0.7 and FDR Ͻ 0.05) (Fig.…”
Section: Molecular and Cellular Proteomics 1810 1955supporting
confidence: 90%
“…The distribution for 6903 intersecting features is depicted in Fig. 5A with average correlation of 0.5 and a mode at 0.9 demonstrating better correlation than previously published for somatic cells (0.4) (49)or differentiating cells (0.2) (48), but in line with our previous study (50). PCA analysis was performed on differentially expressed features, which display good correlation (R Ͼ 0.7 and FDR Ͻ 0.05) (Fig.…”
Section: Molecular and Cellular Proteomics 1810 1955supporting
confidence: 90%
“…Several previous studies have validated SOMAscan using other orthogonal proteomic platforms, including LC-MS/MS and ELISA 5 11 . In an analysis of human embryonic and mesenchymal stem cells, Billing and colleagues considered 408 proteins measured by SOMAscan, LC-MS/MS, and RNA sequencing and reported that 60% of the SOMAscan results were validated by the other two methods, which was comparable to results obtained when comparing LC-MS/MS and RNA sequencing to each other 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have validated SOMAscan using other orthogonal proteomic platforms, including LC-MS/MS and ELISA 5 11 . In an analysis of human embryonic and mesenchymal stem cells, Billing and colleagues considered 408 proteins measured by SOMAscan, LC-MS/MS, and RNA sequencing and reported that 60% of the SOMAscan results were validated by the other two methods, which was comparable to results obtained when comparing LC-MS/MS and RNA sequencing to each other 5 . Murota and colleagues used SOMAscan to identify 33 biomarkers associated with rheumatoid arthritis and selected five proteins to validate the results using conventional immunoassays, including electrochemiluminescence assays, ELISA, and latex turbidimetric assays 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multiplex biological assays were recently combined with MS for the identification of molecules having a biological response and biomarkers of health relevance in an effect-directed approach. For example, gene reporter assays combined with LC-HRMS for determining bioactive estrogenic and anti-estrogenic compounds in environmental water samples (Jonker et al, 2015), cell-based reporter gene assays combined with LC-MS for studying metabolites of the human histamine H4 receptor ligands (Nijmeijer et al, 2012), and a multiplatform approach for protein biomarkers discovery using SOMAscan, a multiplexed aptamer-based technique, and LC-MS (Billing et al, 2016, McArdle et al, 2016). By looking at biological response molecules it can drive future studies on the biological systems affected by exposures (Rappaport, 2012) (Dennis et al, 2016a).…”
Section: Future Perspectivesmentioning
confidence: 99%